Analysis of the Development of Tourist Flow to Lake Toba on the Economic Development of North Sumatra - Dhea Putri Pratama Dance (ProBisnis : Jurnal Manajemen, 2020)
Lake Toba is a tourist area in the province of North Sumatra which has great potential. This can be seen from the development of Lake Toba as a world tourist destination. This research method uses descriptive method, descriptive analysis is to describe all the information data obtained in the form of percentages, average graphs, and others. This research was conducted in Lake Toba, North Sumatra. The results of this study indicate that the development of tourist flows to Lake Toba on the economic development of North Sumatra, indicates a positive impact on the economic development of North Sumatra, this can be seen from the increase in per capita GRDP in the province of North Sumatra, and the increase in tourist visits.